Nutritional Status, Dietary Habits and Sanitation Practices of Adolescent Girls in Sunamganj District of Bangladesh - Abdur Razzak; Preyam Saha; Shakir Moazzem; Md Belal; Amin Raza; Keya Rani Roy; Ali Haider; Oliullah Numan; Kazi Abul Kalam; Wahidu Zaman (International Journal of Nutrition Sciences, 2020)
Background: Problems related to nutrition and personal hygiene are widespread among adolescent Bangladeshi girls. This study assessed the nutritional status, dietary habits, and sanitation practices of adolescent girls of Sunamganj District in Bangladesh.Methods: Totally, 380 adolescent 11-18-year-old girls from 4 different schools and madrasas of Sunamganj District in Bangladesh were randomly enrolled. A structured questionnaire and standard anthropometric methods were used to collect the data. Results: Totally, 4.2%, 26.6%, 1.3%, 7.8%, 7.5%, 3.2% and 20.1% of girls were ‘severely stunted’, ‘stunted’, ‘obese’, ‘overweight’, ‘thin’, ‘severely thin’ and ‘in the risk of being thinness’, respectively. Most of girls came from humble socio-economic backgrounds and over two-thirds of their parents were ‘below primary’ or ‘up to primary’ educational level. Regarding nutritional knowledge, 32.8% of girls’ performance was ‘poor’, whereas 55.5% were ‘average’. The Individual Dietary Diversity (IDD) of 33.8%, 23.4%, and 42.9% of girls were ‘poor’, ‘medium’, and ‘high’, respectively. The Food Consumption Score (FCS) of 0.6%, 11.7%, and 87.7% of girls fell within ‘poor’, ‘borderline’, and ‘acceptable’ categories,respectively. Regarding sanitation practices during the menstrual period, 26.9%, 1.9%, 17.9%, and 39.9% of girls used ‘old clothes’, ‘tissue papers’, ‘new clothes’, and ‘napkin pads’, respectively, while 86%, 29.5%, and 80.2% of girls habitually washed their hands with soap ‘after excretion’, ‘before preparing food’ and ‘before eating meals’, respectively.Conclusion: High percentages of girls were still undernourished because of their lower socio-economic conditions and due to lack of knowledge and awareness on personal hygiene.